A review and analysis of cryptosporidiosis outbreaks in New Zealand. - Garcia-R JC; Hayman DTS (Cambridge University Press, 2023)
Cryptosporidium is a leading global cause of diarrhoea with many reported outbreaks related to water and zoonotic transmission. This study summarizes data from Public Health Surveillance reports since 2010 in New Zealand to describe exposures associated with human diarrhoea outbreaks caused by Cryptosporidium. We investigate the species and subtypes of cases involved in some of the outbreaks to elucidate transmission routes and the predominant aetiological agents of cryptosporidiosis. For the period 2010–2017, 318 cryptosporidiosis outbreaks were reported in New Zealand resulting in 1634 cases and 20 hospitalizations. The most important mode of transmission was person-to-person (primary infections and secondary or close contacts infections), relating to 260 outbreaks and 1320 cases, followed by 113 outbreaks associated with animals, resulting in 436 human cases. From 2018 to 2021, there were 37 cryptosporidiosis outbreaks associated with 324 cases. We identified the subtypes by using polymerase chain reaction targeting the gp60 gene and the likelihood of mixed subtype infections with the Tracking of Indels by DEcomposition (TIDE) algorithm. Subtype families Ib and Ig of Cryptosporidium hominis and IIa and IId of Cryptosporidium parvum were found among cases; however, C. hominis subtypes occurred in 8 of the 11 outbreaks reviewed where molecular data were available. Examination of the chromatograms showed no mixed subtype infections in the samples assessed. Subtyping data need to be routinely incorporated into national surveillance programmes to better understand the epidemiology, sources, transmission and extent of cryptosporidiosis outbreaks in New Zealand. Our study highlights the value of integrating epidemiological information and molecular typing to investigate and manage clusters of cryptosporidiosis cases.
Keywords: Cryptosporidiosis; New Zealand; TIDE analysis; molecular typing; outbreaks; surveillance; Animals; Humans; Cryptosporidiosis; Cryptosporidium; Diarrhea; Disease Outbreaks; DNA, Protozoan; Feces; Genotype; New Zealand